Bibliometric Analysis: The Evolution of Entrepreneurship among Islamic Boarding School Students from an Islamic Economic Law Perspective - Abroza, Ahmad; Mas'ud, Ibnu (Al-Muamalat: Jurnal Ekonomi Syariah, 2024)
The increasing interest in entrepreneurship among students of Islamic boarding schools within the framework of Islamic economics has garnered significant scholarly attention. This research employs bibliometric analysis by accessing the Scopus database to examine research trends related to entrepreneurship among Islamic boarding school students from 1996 to 2024. The aim is to identify research trends related to entrepreneurship among students. The research results indicate a growing interest in student entrepreneurship in Islamic boarding schools, particularly in 2019 and 2022. The focus is on entrepreneurial orientation, knowledge management, innovation, implementation strategies, and organizational performance. Visualization network analysis is highly relevant to the Islamic Economic Law Perspective and efforts to combine religious values with modern business principles in the context of Islamic boarding schools. This research has broad implications, not only for developing theory and understanding of Islamic entrepreneurship but also for shaping practices and policies that support entrepreneurship development based on Islamic values in Islamic boarding schools and the general public.